2020
DOI: 10.1136/gutjnl-2020-321402
|View full text |Cite
|
Sign up to set email alerts
|

Serum glucose excretion after Roux-en-Y gastric bypass: a potential target for diabetes treatment

Abstract: ObjectiveThe mechanisms underlying type 2 diabetes resolution after Roux-en-Y gastric bypass (RYGB) are unclear. We suspected that glucose excretion may occur in the small bowel based on observations in humans. The aim of this study was to evaluate the mechanisms underlying serum glucose excretion in the small intestine and its contribution to glucose homeostasis after bariatric surgery.Design2-Deoxy-2-[18F]-fluoro-D-glucose (FDG) was measured in RYGB-operated or sham-operated obese diabetic rats. Altered gluc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 31 publications
4
25
0
Order By: Relevance
“…In the i.p. protocol, we found that a minor portion of 18 FDG was counter-transported from blood to GI lumen, which confirms previous observations in rodents and humans [14,17]. It remains to be demonstrated whether the leakage of glucose from the circulation, and its putative increase in diseased states (e.g., hyperglycemia) might influence the intestinal milieu and GI function, or whether glucose excretion may become a potential target in disease states, as suggested by observations in bariatric surgery studies [14].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the i.p. protocol, we found that a minor portion of 18 FDG was counter-transported from blood to GI lumen, which confirms previous observations in rodents and humans [14,17]. It remains to be demonstrated whether the leakage of glucose from the circulation, and its putative increase in diseased states (e.g., hyperglycemia) might influence the intestinal milieu and GI function, or whether glucose excretion may become a potential target in disease states, as suggested by observations in bariatric surgery studies [14].…”
Section: Discussionsupporting
confidence: 92%
“…In addition, the administration of a single glucose or standard meal, passing through the GI tract, has been associated with systemic and liver inflammation [ 11 , 12 ], though it remains to be established whether these effects require specifically the GI entry route. Accumulating evidence from, e.g., bariatric surgery [ 13 , 14 , 15 ] or drugs affecting GI function (GLP1 agonists [ 15 , 16 ], metformin [ 17 , 18 , 19 , 20 ]), point to the GI tract as an important regulator of tissue glucose uptake (GU).…”
Section: Introductionmentioning
confidence: 99%
“…RYGB surgery improves metabolic health and diabetes remission more effectively than other treatment strategies, including pharmacotherapy and lifestyle interventions [25,26]. Several murine RYGB studies show a positive impact of the surgery on various metabolic parameters reducing the risk of type 2 diabetes mellitus [27][28][29] and hyperlipidemia [30]. RYGB surgery leads to reduced glycemia, as shown by functional studies of the liver and brain.…”
Section: Introductionmentioning
confidence: 99%
“…Because RYGB reduces stomach size and excludes the duodenum from contact with ingested food, physical restriction and malabsorption of nutrients, respectively, were originally thought to mainly account for its beneficial effects on energy and glucose homeostasis [ 6 ]. With the aid of rodent models of RYGB, however, it is becoming increasingly evident that complex changes in various molecular, cellular, and systems processes take place postoperatively [ 7 , 8 , 9 , 10 ], better understanding of which may guide the development of more effective, noninvasive treatments against metabolic disease.…”
Section: Introductionmentioning
confidence: 99%